2021
DOI: 10.1038/s41598-021-85189-3
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal change of occipitocervical parameters after anterior cervical discectomy and fusion

Abstract: To evaluate the reciprocal changes in occipitocervical parameters according to the recovery of cervical lordosis (CL) after anterior cervical discectomy and fusion (ACDF) in patients with sagittal imbalance. Sixty-five cases that underwent ACDF were followed. They were divided according to the recovery of the CL: Group 1 (ΔCL > 5°, 30 cases) and Group 2 (ΔCL < 5°, 35 cases). The following parameters were measured: occiput-cervical inclination (OCI), CL, occiput-C2 angle (OC2A), distance between external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…41 After a patient recovers optimal cervical lordosis (CL), C0-2 angle reciprocally decreases. 22 Concurrently, Lafage et al 23 reported that correction of sagittal cervical deformity (CD) led to reciprocal relaxation of the established CD compensatory mechanisms such as C0-2 hyperlordosis and thoracic hypokyphosis. 23 Furthermore, the preoperative Neck Disability Index (NDI) had a significant correlation with preoperative C0-2 range of motion (ROM) and reserve of extension (ROE).…”
Section: Compensatory Mechanisms and Reciprocal Changes Of The Cervic...mentioning
confidence: 99%
See 4 more Smart Citations
“…41 After a patient recovers optimal cervical lordosis (CL), C0-2 angle reciprocally decreases. 22 Concurrently, Lafage et al 23 reported that correction of sagittal cervical deformity (CD) led to reciprocal relaxation of the established CD compensatory mechanisms such as C0-2 hyperlordosis and thoracic hypokyphosis. 23 Furthermore, the preoperative Neck Disability Index (NDI) had a significant correlation with preoperative C0-2 range of motion (ROM) and reserve of extension (ROE).…”
Section: Compensatory Mechanisms and Reciprocal Changes Of The Cervic...mentioning
confidence: 99%
“…Hyperlordotic positioning of the upper cervical spine leads to a kyphotic alignment of the subaxial spine to maintain balanced cervical alignment [ 41 ]. After a patient recovers optimal cervical lordosis (CL), C0–2 angle reciprocally decreases [ 22 ]. Concurrently, Lafage et al [ 23 ] reported that correction of sagittal cervical deformity (CD) led to reciprocal relaxation of the established CD compensatory mechanisms such as C0–2 hyperlordosis and thoracic hypokyphosis [ 23 ].…”
Section: Compensatory Mechanisms and Reciprocal Changes Of The Cervic...mentioning
confidence: 99%
See 3 more Smart Citations